Acute toxicity of Psilocybe cubensis (Ear.) Sing., Strophariaceae, aqueous extract in mice - Kirsten,Thiago Berti (2010)
Psilocybe cubensis (Ear.) Sing., Strophariaceae, is a hallucinogen mushroom that has been used since the old times by humans, causing several psychotic effects. P. cubensis contains two tryptamine derivates: psilocybin and psilocin, agonists of the 5-HT2 receptor (serotonin). The main objective of this study was to investigate the acute toxicity effects of P. cubensis aqueous extract (PCAE) administration in mice. Male and female adult Swiss mice received PCAE 0.1 mL/10 g i.p., and were observed individually, directly in a glass box and in an open-field. In relation to the data of the control group, PCAE-treated animals presented: an increased gnawing, appearance of wet-dog shakes and a decreased locomotion and rearing frequencies after 29-38 min. Also a clear gender difference was detected, being female mice more sensible to the PCAE than males. It was suggested that PCAE administration produced specific effects on mice behaviors, characteristic of drugs which interfere on central serotonergic and dopaminergic systems. Finally, the observational methods here employed were efficient to evaluate the toxic effects of the extract.